Utilization of the Mpu Purwa Museum as a source of social studies learning based on local wisdom - Deny Yuniar Satriyani; Alrianingrum, Septina; Khotimah, Kusnul (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
Contextual learning is a focus for improving learning quality. The quality of social studies learning in junior high schools needs to be encouraged to enhance students' learning interests and learning experiences. Social studies learning can be directed by utilizing the potential of the surrounding environment. The Mpu Purwa Museum, a local wisdom in Malang, can serve as a supporting learning resource. The context of learning at the Mpu Purwa Museum focuses on local history and Hindu-Buddhist cultural heritage. Classroom learning, which is theoretical and less engaging, must be integrated with students' learning experiences. This research employed a descriptive qualitative method. Data collection was conducted through direct observation and in-depth interviews during museum visits, supplemented by documentation. The subjects were eighth-grade students of SMP 20 Malang, as it was relevant to the material taught in school. Furthermore, as a bridge between theory and classroom learning, the Mpu Purwa Museum is an appropriate choice for students to implement their knowledge. The results indicate that a visit to the Mpu Purwa Museum as a primary learning resource creates a contextual and meaningful learning experience.